VeggieTales. The little drummer boy [videorecording (DVD)] - Roberts, Brian K; Nawrocki, Michael; Vischer, Phil; Vischer, Lisa (Big Idea's VeggieTales., 2011)
Junior Asparagus stars as The Little Drummer Boy, a lonely child who finds the true meaning of Christmas when he stumbles upon the birth of the baby Jesus. A story of generosity, hope, and love, this timeless tale will warm the hearts of children everywhere!